Dark energy survey internal consistency tests of the joint cosmological probes analysis with posterior predictive distributions. Issue 2 (24th February 2021) - Doux, C; Baxter, E; Lemos, P; Chang, C; Alarcon, A; Amon, A; Campos, A; Choi, A; Gatti, M; Gruen, D; Jarvis, M; MacCrann, N; et al.
ABSTRACT: Beyond ΛCDM, physics or systematic errors may cause subsets of a cosmological data set to appear inconsistent when analysed assuming ΛCDM. We present an application of internal consistency tests to measurements from the Dark Energy Survey Year 1 (DES Y1) joint probes analysis. Our analysis relies on computing the posterior predictive distribution (PPD) for these data under the assumption of ΛCDM. We find that the DES Y1 data have an acceptable goodness of fit to ΛCDM, with a probability of finding a worse fit by random chance of p  = 0.046. Using numerical PPD tests, supplemented by graphical checks, we show that most of the data vector appears completely consistent with expectations, although we observe a small tension between large- and small-scale measurements. A small part (roughly 1.5 per cent) of the data vector shows an unusually large departure from expectations; excluding this part of the data has negligible impact on cosmological constraints, but does significantly improve the p -value to 0.10. The methodology developed here will be applied to test the consistency of DES Year 3 joint probes data sets.